When seeing is not believing: application-appropriate validation matters for quantitative bioimage analysis - Chen, Jianxu; Viana, Matheus P.; Rafelski, Susanne M. (Nature methods, 2023)
A key step toward biologically interpretable analysis of microscopy image-based assays is rigorous quantitative validation with metrics appropriate for the particular application in use. Here we describe this challenge for both classical and modern deep learning-based image analysis approaches and discuss possible solutions for automating and streamlining the validation process in the next five to ten years.